Assessing the Time‐Dependent Impact of Performance Status on Outcomes After Liver Transplantation. Issue 4 (30th June 2020) - Wallace, David; Cowling, Thomas; McPhail, Mark J.; Brown, Sarah E.; Aluvihare, Varuna; Suddle, Abid; Auzinger, Georg; Heneghan, Michael A.; Rowe, Ian A.; Walker, Kate; Heaton, Nigel; van der Meulen, Jan; et al.
Abstract : Background and Aims: Identifying how the prognostic impact of performance status (PS) differs according to indication, era, and time period ("epoch") after liver transplantation (LT) could have implications for selection and treatment of patients on the waitlist. We used national data from the United Kingdom and Ireland to assess impact of PS on mortality separately for HCC and non‐HCC recipients. Approach and Results: We assessed pre‐LT PS using the 5‐point modified Eastern Cooperative Oncology Group scale and used Cox regression methods to estimate hazard ratios (HRs) that compared posttransplantation mortality in different epochs of follow‐up (0‐90 days and 90 days to 1 year) and in different eras of transplantation (1995‐2005 and 2006‐2016). 2107 HCC and 10, 693 non‐HCC patients were included. One‐year survival decreased with worsening PS in non‐HCC recipients where 1‐year survival was 91.9% (95% confidence interval [CI], 88.3‐94.4) in those able to carry out normal activity (PS1) compared to 78.7% (95% CI, 76.7‐80.5) in those completely reliant on care (PS5). For HCC patients, these estimates were 89.9% (95% CI, 85.4‐93.2) and 83.1% (95% CI, 61.0‐93.3), respectively. Reduction in survival in non‐HCC patients with poorer PS was in the first 90 days after transplant, with no major effect observed between 90 days and 1 year. Adjustment for donor and recipient characteristics did not change the findings. Comparing era, post‐LT mortality improved for HCC (adjusted HR, 0.55; 95% CI, 0.40‐0.74) and non‐HCC recipients (0.48; 95% CI, 0.42‐0.55), but this did not differ according to PS score ( P = 0.39 and 0.61, respectively). Conclusions: Impact on mortality of the recipient's pretransplant PS is principally limited to the first 3 months after LT. Over time, mortality has improved for both HCC and non‐HCC recipients and across the full range of PS.